If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 = 2x + -3 Reorder the terms: 10 = -3 + 2x Solving 10 = -3 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 10 + -2x = -3 + 2x + -2x Combine like terms: 2x + -2x = 0 10 + -2x = -3 + 0 10 + -2x = -3 Add '-10' to each side of the equation. 10 + -10 + -2x = -3 + -10 Combine like terms: 10 + -10 = 0 0 + -2x = -3 + -10 -2x = -3 + -10 Combine like terms: -3 + -10 = -13 -2x = -13 Divide each side by '-2'. x = 6.5 Simplifying x = 6.5
| 12=156h | | -4x-32=-72 | | 3g-2(g+4)=8(g-1) | | 7m=-35 | | 4(1+-3.5y)+2y=-2 | | -2f+6=10 | | 4e=32 | | 3x+5=69-5x | | 10n-8= | | 3m-6=5m+8 | | 16p=240 | | 3+7x=45+x | | 480=(7-1)c | | 2x-5=12x-95 | | 2x+7y=2 | | 3y^2+20y+73=0 | | 10x+41=1 | | -2x^2+6x=-40 | | 10n+6.2= | | 4(2.5+y)-4y=9 | | 2(11x+2y-2)+7x+4=180 | | X^2+5x+6-10x=0 | | m+3=-m-1 | | x*3= | | 5x+66=10x+11 | | 2(11x+2y+2)+7x+4=180 | | 14b=16b+72 | | X^2+5x+6=10x | | 12x+6=6x+24 | | 44.7-10n= | | -3x-4=11 | | 12x+-19=3x+8 |